Determination of the performance of biodegradation of lubricant oil residues retained in bentonite using the oil eating microbes (Rodhococus, Pseudomonas, and Bacillus) bacterial consortium. - Chirre Flores, Jaqueline Heidy (2022)
Oils used as lubricants in machinery, vehicles, or industrial equipment deteriorate with use; that is, they lose their properties due to the effect of environmental conditions; and acids and oxidation compounds, that can be corrosive and are considered hazardous waste, are formed. This research seeks to determine the biodegradation performance of used automotive lubricating oil by the Oil Eating Microbes (Rhodococcus, Pseudomonas, and Bacillus) bacterial consortium quantifying the total petroleum hydro[1]carbons (TPH) retained in bentonite in four experimental tests. A 57 % TPH decrease was obtained in the following conditions: T = 35 ºC, pH = 7,0, mechanical agitation = 120 rpm, and dilution of the contaminated clay in water in a ratio of 1 (clay): 3 (water).